Non traumatic pathological sternoclavicular joint dislocation an unexplored complication of clavicle osteomyelitis-a case report - Sivabalaganesh Amirthalingam,; Suriyakumar, Sundar; Harshavardhan, Giriraj; Manickam, Karthikeyan (International Journal of Research in Orthopaedics, 2023)
Non-traumatic pathological sternoclavicular joint dislocation due to medial end of clavicle osteomyelitis is extremely rare. This kind of rare complication should be anticipated while encountering these kinds of cases. A sixty-three-year-old male came with pain and swelling over the left neck and was diagnosed to have left clavicle osteomyelitis. The unexplored complication of sternoclavicular joint dislocation and successful management of such complications has been discussed in this case report. To best of our knowledge this is the first case report of a non-traumatic pathological sternoclavicular joint dislocation due to clavicle osteomyelitis. This case report will supplement the inadequate literature in management of such cases.